Serum C‐reactive protein in dogs with paraplegia secondary to acute intervertebral disc extrusion - Foreman, Max (J Vet Intern Med, 2021)
BACKGROUND: Apart from the absence of nociception, there is no readily available prognostic test for dogs presenting with paraplegia secondary to acute intervertebral disc extrusion (IVDE). OBJECTIVE: To assess if serum C‐reactive protein (CRP) can predict the postoperative outcome in paraplegic dogs undergoing surgery for IVDE and to assess the association between serum CRP and presence/absence of nociception on admission, and serum CRP and presence/absence of intramedullary changes seen on magnetic resonance imaging (MRI). ANIMALS: One hundred dogs that underwent surgery at our hospital between 2018 and 2020 because of acute paraplegia secondary to IVDE and in which serum CRP was measured. METHODS: Retrospective observational cohort study. Dogs were classified as 4 or 5 according to the modified Frankel score (MFS) depending on presence/absence of nociception, respectively. MRI images were reviewed and the T2‐weighted hyperintensity: L2 vertebral body length was measured. Postoperative outcome was defined as positive if nociception, ambulation or both returned after decompressive surgery. RESULTS: The median (95% CI) serum CRP was 4 (4‐5) and 6 (4‐7) mg/L in MSF4 and MSF5, respectively (P = .03). A weak linear relationship (R (2) = 0.049, P = .03) was found between CRP and the T2‐weighted hyperintensity: L2 vertebral length. Outcome data was available for 85 dogs: CRP was 4 (4‐5) and 5 (4‐10) mg/L in positive and negative outcome dogs, respectively (P = .32). CONCLUSION AND CLINICAL IMPORTANCE: Serum CRP did not predict outcome after surgery in dogs with paraplegia secondary to IVDE.